Larval dispersal model of coral Acropora in the Karimunjawa Waters, Indonesia - Elis Indrayanti; MUHAMMAD ZAINURI; AGUS SABDONO; DIAH PERMATA WIJAYANTI; WIDODO SETIYO PRANOWO; HENDRY SYAHPUTRA ROPINUS SIAGIAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Indrayanti E, Zainuri M, Sabdono A, Wijayanti DP, Pranowo WS, Siagian HSR. 2019. Larval dispersal model of coral Acropora in the Karimunjawa Waters, Indonesia. Biodiversitas 20: 2068-2075. Identification of connectivity patterns through the larval dispersal dynamics is urgently needed to support the sustainable larval supply. Many studies on the larval coral distribution have been reported. However, no study of coral larval dispersal has been conducted in Karimunjawa. The purpose of this research was to build a model of coral larval dispersal in Karimunjawa waters. Modeling was carried out by using a 2-dimensional hydrodynamic current approach with a particle tracking module. The larval release was conducted during the full moon in the first transition period (April) and the second transition period (October). The larval source was assumed from around Sambangan waters. Modeling validation was done by comparing the model results to the direct of current measurements with Acoustic Doppler Current Profiler (ADCP). The results of larval dispersal model showed that both the transition seasons I and II were similar in the direction of movement towards the west. This result indicated that currents, tides, and winds influenced the larval dispersal process. Also, the model results showed that Sambangan, Tengah, Cilik, Sintok, the west site of Karimun, Menjangan Kecil, and Menjangan Besar Islands were identified as the location of the larval settlement.